Does women empowerment alone influence contraception utilization in Bangladesh perspective? Findings from the 2017–2018 Demographic Health Survey using a structural equation model analysisAJOG Global Reports at a Glance - Md. Nawal Sarwer, MPH; Effat Ara Jahan, MSc; Akibul Islam Chowdhury, MSc (AJOG Global Reports)
BACKGROUND: Women empowerment is a crucial issue that is less studied as a factor of contraceptive use among married women that helps to achieve sustainable development goals. OBJECTIVE: This study aimed to assess the relationship between women empowerment and contraceptive use. STUDY DESIGN: This cross-sectional study used 2017–2018 Bangladesh Demographic and Health Survey data, which included 12,006 women (weighted) aged 15 to 49 years. Hierarchical logistic regression and structural equation models were used to show the relationship between women empowerment and contraceptive use. RESULTS: Overall, increased use of contraception was associated with increased age, urban residence, increased wealth index, and education level of both the husband and wife. After controlling individual and locality factors, the findings from the regression model showed that women empowerment in terms of women decision-making, attitude toward violence, and social independence significantly influences contraceptive use (P<.05). However, the structural equation model analysis revealed a negative but nonsignificant relationship between overall women empowerment and contraceptive use (β=−0.138; P>.05). CONCLUSION: This study implies that greater women empowerment may not always act as a stronger determinant of contraceptive use, and therefore, other contributing factors, such as age, education, religion, husband's participation, joined decision-making, economic status, and couple relationship, should be considered.